(untitled) (Marketing Journal, 2025)
This article systematizes internal and external factors influencing the development of the food industry. It examines the impact of innovations, labor market changes, shifts in consumer demand, resources, and environmental factors on the development of the food industry at both global and local levels. The influence of various factors on the industry is assessed, and strategic recommendations for advancing the sector are provided.